Efforts to Increase the Social Care of Middle School Students with Classical Guidance Service Tools - Baiq Juliana (Department of Guidance and Counseling, FIP, Undiksha, 2023)
It is necessary to help students from all parties, especially supervising and supervising teachers. The goal is that students are aware of the growth and development of a sense of social welfare, especially in the school environment and its surroundings. The purpose of this research is to develop and test the acceptability and effectiveness of classic counseling tools to increase the social well-being of high school students. This research is a type of research that uses 4D development methods (Define, Design, Develop and Disseminate). This study involved 3 experts in the field of guidance and counseling and 2 people who tested the acceptance of classic counseling tools. In this study, data was collected using a questionnaire, which was analyzed using the Content Validity Ratio (CVR) formula. The results of the content validity index (CVI) and independent t.CVR analysis showed that all the goal statements in the questionnaire were accepted and received a CVI score of 1 category very good or exceptional, so the classical teaching device corresponds to acceptance criteria. The effectiveness of the Classical Tutoring Service device was tested on 30 Grade IX students of SMP Negeri 2 Singarajan using a Pretest-Posttest Control Group Design experimental design. The results of the t-test show a significant value of 0.00, which means that the use of classic counseling services tools is effective in increasing the social well-being of high school students.